Knockdown of estrogen receptor β increases proliferation and affects the transcriptome of endometrial adenocarcinoma cells - Treeck, Oliver (BMC Cancer, 2019)
BACKGROUND: Estrogen receptor β (ERβ) has been repeatedly suggested to play important roles in hormone-dependent cancer like in tumors of the breast, ovary or prostate. In this study, we intended to further elucidate its role in endometrial cancer. METHODS: For this purpose, we knocked down ERβ expression in two endometrial cancer cell lines, the ERα-negative/ERβ-positive line HEC-1A and the ERα/β-positive cell line RL95/2, by means of siRNA transfection. Cell proliferation after transfection was assessed using the fluorescent CTB Assay (Promega). In order to elucidate possible molecular mechanisms which might underlie the effect on proliferation, we performed transcriptome analyses by means of human Affymetrix Human Gene Chip 2.0. Additionally, we treated the employed cell lines with different ERβ modulators to examine their effect on proliferation. RESULTS: siRNA-mediated knockdown of ERβ significantly increased proliferation of both endometrial cancer cell lines. In HEC-1A cells, proliferation was significantly increased 4, 5 and 6 days after transfection, with a maximum of about 1.7-fold (p < 0.05) on day 6. Endometrial RL95/2 cells with an ERβ knockdown exhibited a clearly enhanced proliferation on day 3 and days 4 to 8, when even 2.4-fold higher numbers of viable cells were detected (p < 0.01). Transcriptome analysis revealed that this was accompanied by increased expression of several genes being known to be upregulated in cancer, including proliferation-associated genes and oncogenes, and by repression of genes associated with differentiation, apoptosis or growth inhibition. Corroborating the observed knockdown effects, treatment with the ERβ antagonists PHTTP and (R, R) THC was also able to induce proliferation of both cell lines. CONCLUSIONS: Our data clearly support the putative role of ERβ as tumor suppressor in endometrium as previously suggested in studies on other tissues and encourage further studies to find out to what extent this molecule might be a potential therapy target in this cancer entity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-019-5928-2) contains supplementary material, which is available to authorized users.